Measuring confidence and uncertainty during the financial crisis: Evidence from the CFS survey - Horst Entorf; Christian Knoll; Liliya Sattarova (Goethe University Frankfurt, Center for Financial Studies (CFS), 2011)
The CFS survey covers individual situations of banks and other companies of the financial sector during the financial crisis. This provides a rare possibility to analyze appraisals, expectations and forecast errors of the core sector of the recent turmoil. Following standard ways of aggregating individual survey data, we first present and introduce the CFS survey by comparing CFS indicators of confidence and predicted confidence to ifo and ZEW indicators. The major contribution is the analysis of several indicators of uncertainty. In addition to well established concepts, we introduce innovative measures based on the skewness of forecast errors and on the share of 'no response' replies. Results show that uncertainty indicators fit quite well with pattern of real and financial time series of the time period 2007 to 2010.
urn:nbn:de:hebis:30-103360
Keywords: G01; G17; G21; 330; Business Sentiment; Financial Crisis; Survey Indicator; Uncertainty